Influenza H1N1 virus-associated pneumonia often resembles rapidly progressive interstitial lung disease seen in collagen vascular diseases and COVID-19 pneumonia; CT-pathologic correlation in 24 patients - Murota, Makiko (Eur J Radiol Open, 2020)
PURPOSE: To describe computed tomography (CT) findings of influenza H1N1 virus-associated pneumonia (IH1N1VAP), and to correlate CT findings to pathological ones. METHODS: The study included 24 patients with IH1N1VAP. Two observers independently evaluated the presence, distribution, and extent of CT findings. CT features were divided into either classical form (C-form) or non-classical form (NC-form). C-form included: A.) broncho-bronchiolitis and bronchopneumonia type, whereas NC-forms included: B.) diffuse peribronchovascular type, simulating subacute rheumatoid arthritis-associated (RA) interstitial lung disease (ILD) and C.) lower peripheral and/or peribronchovascular type, resembling dermatomyositis-associated ILD and COVID-19 pneumonia. In 10 cases with IH1N1VAP where lung biopsy was performed, CT and pathology findings were correlated. RESULTS: The most common CT findings were ground-glass opacities (24/24, 100 %) and airspace consolidation (23/24, 96 %). C-form was found in 11 (46 %) patients while NC-form in 13 (54 %). Types A, B, and C were seen in 11(46 %), 4 (17 %), and 9 (38 %) patients, respectively. The lung biopsy revealed organizing pneumonia in all patients and 6 patients (60 %) showed incorporated type organizing pneumonia that was common histological findings of rapidly progressive ILD. CONCLUSION: In almost half of patients of IH1N1VAP, CT images show NC-form pneumonia pattern resembling either acute or subacute RA or dermatomyositis-associated ILD and COVID-19 pneumonia.